2017
DOI: 10.1155/2017/9015891
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Offshore Advection of Boundary Layer Rolls over a Stably Stratified Sea Surface

Abstract: Streaky structures of narrow (8-9 km) high wind belts have been observed from SAR images above the Baltic Sea during stably stratified conditions with offshore winds from the southern parts of Sweden. Case studies using the WRF model and in situ aircraft observations indicate that the streaks originate from boundary layer rolls generated over the convective air above Swedish mainland, also supported by visual satellite images showing the typical signature cloud streets. The simulations indicate that the rolls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Additionally, as shown by Högström et al, the stratification during conditions with large land‐water temperature difference might be extremely strong, such that a special turbulence regime ensues described as quasi–two dimensional, decorrelated from layers in the vertical. In Svensson et al, it is shown that advected convective structures persist up to 100 km over the stable sea surface. The offshore environment can therefore be complex with effects with different origins taking place in different layers of the atmosphere.…”
Section: Mesoscale Wind Field Modificationsmentioning
confidence: 98%
“…Additionally, as shown by Högström et al, the stratification during conditions with large land‐water temperature difference might be extremely strong, such that a special turbulence regime ensues described as quasi–two dimensional, decorrelated from layers in the vertical. In Svensson et al, it is shown that advected convective structures persist up to 100 km over the stable sea surface. The offshore environment can therefore be complex with effects with different origins taking place in different layers of the atmosphere.…”
Section: Mesoscale Wind Field Modificationsmentioning
confidence: 98%
“…Examples are processes generated by air-sea temperature contrasts, such as sea breeze circulations, low-level jets (LLJs, e.g. K€ allstrand et al, 2000) or horizontal rolls (Svensson et al, 2017). Coastal areas are influenced by riverine outflow resulting in respiration of terrestrial organic carbon inputs, benthic-pelagic coupling, variability in surfactant abundance and near-surface vertical stratification (Rutgersson et al, 2011).…”
Section: Category Characterizationmentioning
confidence: 99%
“…Their analyses of airborne data suggest that roll vortices may be a significant factor modulating the air-sea momentum exchange. Recently, Svensson et al (2017) presented results concerning roll persistence during situations with advection to a strongly stratified boundary layer via SAR and aircraft data. Gao et al (2017) studied the impact of rolls on the intensification process of the TC's and identified a pathway by which rolls can affect the structure and the intensification of the simulated TC's.…”
Section: Introductionmentioning
confidence: 99%